Reflections of COVID-19 Pandemic on Autism Spectrum Disorder: A Descriptive Case Study - Sunagül SANI-BOZKURT; Gülden BOZKUŞ-GENÇ; Gizem YILDIZ (Anı Publishing, 2021)
The aim of this study was to explore type of studies implemented for the autism spectrum disorders (ASD) community by institutions that directly deal with ASD during the COVID-19 pandemic in Turkey and in the world. The descriptive case study design was used in the study. The contents on the websites of the institutions were analyzed through document analysis. According to the results, it was observed that the data consisted of supporting contents related to education, health, and public policies regarding the COVID-19 process and that the contents were frequently presented through webinars, visual representations, electronic text sources, online communication platforms, and social media environments. During this process, informative studies were frequently carried out and practical studies were rarely conducted. While it is considered that institutional studies both in Turkey and in the world may serve as an example to other institutional studies, it is considered that the diversity of these examples should be increased through cooperation between institutions.